2023
DOI: 10.1039/d3sm00191a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sample height and particle elongation in the sedimentation of colloidal rods

Abstract: Complex stacking sequences emerge in sedimented suspensions of colloidal rods due to the interplay between between gravity and bulk phenomena.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…78 Eckert et al showed the effect of gravitational fields on bulk phase behavior of NRs to cause NRs to layer on top of each other as sedimentation occurs to form sedimentation stacks with the ends most likely vertically. 79 These stacks mimic a top-down approach to selfassembly 13,18,19,21,80−83 using the bottom layer of NRs as the adherent surface to build up the more linkages as gravitational forces bring them down to the bottom 78 and electrostatic forces generate an amplified electric field for in-solution streptavidin to localize and bind to the ends of the NRs for self-assembly of longer chains to occur. 11,84,85 Kinetics of the self-assembly process at short times was monitored by extinction spectroscopy (Figure 8a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…78 Eckert et al showed the effect of gravitational fields on bulk phase behavior of NRs to cause NRs to layer on top of each other as sedimentation occurs to form sedimentation stacks with the ends most likely vertically. 79 These stacks mimic a top-down approach to selfassembly 13,18,19,21,80−83 using the bottom layer of NRs as the adherent surface to build up the more linkages as gravitational forces bring them down to the bottom 78 and electrostatic forces generate an amplified electric field for in-solution streptavidin to localize and bind to the ends of the NRs for self-assembly of longer chains to occur. 11,84,85 Kinetics of the self-assembly process at short times was monitored by extinction spectroscopy (Figure 8a).…”
Section: Resultsmentioning
confidence: 99%
“…Kinetically, forming a NR to NR bond would initially proceed at a quicker rate to form dimers, with trimers, tetramers, and larger chains all gradually requiring more reaction time to occur. In suspension, dimerization is the main self-assembly pathway. , However, over time, the NRs begin to sediment out of solution, which would be quicker for larger NRs as well as longer chains of NRs based on faster sedimentation rates . Eckert et al showed the effect of gravitational fields on bulk phase behavior of NRs to cause NRs to layer on top of each other as sedimentation occurs to form sedimentation stacks with the ends most likely vertically . These stacks mimic a top-down approach to self-assembly ,,,, using the bottom layer of NRs as the adherent surface to build up the more linkages as gravitational forces bring them down to the bottom and electrostatic forces generate an amplified electric field for in-solution streptavidin to localize and bind to the ends of the NRs for self-assembly of longer chains to occur. ,, …”
Section: Resultsmentioning
confidence: 99%